Use of Pericardial Patch Conduit in Bidirectional Glenn Shunt: An Innovative Technique (Cardiovascular Journal, 2020)
Bidirectional Glenn Shunt is a palliative procedure in single ventricle or hypoplastic right ventricle, tricuspid atresia and pulmonary stenosis complex where definitive repair is not feasible as well as a intermediate step of Fontan procedure. It is done by anastomosing superior venacava with right pulmonary artery or conduit can be used. We were forced to do the anastomosis between superior venacava and left pulmonary artery using a conduit as anatomy wasn’t favorable. Due to unavailability of any recognized conduits we used autologous pericardium and created a conduit with it to carry out anastomosis. Post-operative results were satisfactory.Cardiovasc. j. 2020; 13(1): 92-94